The temporalis muscle and its relationship to the accessory attachments and the main pedicle—a cadaveric study. Issue 6 (June 2020) - Prasidha, Ines; Singla, Apresh; Rawther, Thampi; Ngo, Quan
Summary: Lengthening temporalis myoplasty, described by Daniel Labbe in 1997, is a facial reanimation procedure for the treatment of facial nerve palsy. It involves the mobilization of temporalis muscle antero-inferiorly, and the insertion of its tendon at the nasolabial fold-oral commissure region. Knowledge of the temporalis muscle is crucial in performing this procedure; however, previous anatomical studies are limited. This study on cadavers, aimed to describe the anatomical location of the temporalis muscle insertion in relation to the adjacent structures, and its main pedicle to aid surgeons in performing this procedure. Twenty-four temporalis muscles were dissected in 12 fresh frozen cadavers. The anatomical location of the temporalis muscle insertion, accessory attachments, the emergence of the posterior deep temporal artery, and the distance of sliding movements from the coronoid process to the nasolabial fold were recorded. In addition to its origin from the temporalis fossa and its insertion at the coronoid process, the temporalis muscle was found to have multiple accessory attachments to adjacent structures. These findings explain the challenges in performing the sliding action without releasing the accessory attachments to the masseter and pterygoid muscles. The deep posterior temporal artery is located inferoposteriorly in relation to the muscle. Therefore, the muscle elevation maneuver performed without direct vision can be done with minimal risk to the muscle pedicle. The knowledge of temporalis muscle insertion, its accessory attachments, and its main pedicle will facilitate surgeons in performing the lengthening temporalis myoplasty more confidently.